Bubble jet impact on a rigid wall of different stand-off parameters. Issue 2 (15th January 2015) - Li, S; Wang, S P; Zhang, A M
Abstract: One of the key features of the dynamics of a bubble near a rigid wall is the development of a high liquid jet, generating highly localized pressure on the wall. In present study, the boundary integral method is employed to simulate this phenomenon, and the vortex ring model is introduced to handle the discontinued potential of the toroidal bubble. Meanwhile, the pressure induced in the whole process is calculated by an auxiliary function. The effect of the stand-off parameter on the bubble dynamics and the pressure on the wall is investigated, and a double-peaked structure occurs in the pressure profile after the jet impact in some cases, which is associated with the jet impact and the high internal pressure inside the bubble.